2021
DOI: 10.1080/13218719.2021.1976301
|View full text |Cite
|
Sign up to set email alerts
|

Criminological profile of minors who have committed child-to-parent violence

Abstract: The rise of CPV cases in the last decade has become a matter of concern among researchers, who have investigated prevalence rates and factors related to this type of behavior. This study aims to analyze the criminological profile of the minors who have committed CPV compared to minors who have committed other type of crimes. The participants were 341 juveniles with a disciplinary record in the Juvenile Court of a Spanish province, whose ages ranged from 14 to 17 years old (M ¼ 15.86, SD ¼ 1.02). The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The predictive validity of youth risk assessment tools may change, as the individual weights of specific risk and protective factors may vary across young people [48,49]. While there are very few publications available that address developmental differences in risk assessment in the juvenile offender population, Palanques et al [3] in their study found that the CPV group had mostly committed CPV, whereas the comparison group had tended to commit property crimes. In addition, the results showed that the CPV group had a higher risk profile than the comparison group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The predictive validity of youth risk assessment tools may change, as the individual weights of specific risk and protective factors may vary across young people [48,49]. While there are very few publications available that address developmental differences in risk assessment in the juvenile offender population, Palanques et al [3] in their study found that the CPV group had mostly committed CPV, whereas the comparison group had tended to commit property crimes. In addition, the results showed that the CPV group had a higher risk profile than the comparison group.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the worldwide prevalence of CPV span the range of 5-21%. Specifically, in relation to verbal, psychological, and emotional CPV, the incidence rises to 22-93% [3,4]. In Spain last year, a total of 4332 investigations were opened against young people aged 14-18 for violence within the family [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Craig & Zettler, 2021). Research evidence suggests that the risk factor profiles of adolescents involved in adolescent to parent violence may differ from adolescents involved in other forms of family violence and non-family violence offending behaviors (Contreras & Cano, 2015; Ibabe et al, 2014; Kennedy et al, 2010; Nowakowski-Sims, 2019; Palanques et al, 2021). Nowakowski-Sims (2019) explored childhood adversity and delinquency in two cohorts of adolescents, one involved in adolescent to parent violence and the other sibling-to-sibling violence.…”
Section: Introductionmentioning
confidence: 99%